Anthropometric profiles of elite open-water swimmers - Shaw, G.; Mujika, I. (International Journal of Sports Physiology and Performance, 2018)
Reports detailing the physiques of open-water (OW) swimmers are limited. Data from anthropometric screening around competition provides a unique opportunity to describe the current physical attributes of elite OW swimmers peaking for international competition. Anthropometric screening was undertaken on a group of Australian and French OW swimmers as part of performance monitoring within 2 wk of the 2015 FINA World Championships. Height, mass, and sum of 7 skinfolds were measured using ISAK standardized measurement techniques by 2 trained anthropometrists. Data were collated and compared with previously published data on OW and pool swimmers. French swimmers had lower skinfolds (57.3±6.1 vs 80.5±21.3 mm, P=.0258), were lighter (64.7?±?10.8 vs 74.6±11.8 kg, P=.013), and had lower lean-mass index (LMI) (34.7±7.3 vs 38.2?±?8.8, P=.035) than Australian swimmers. Male and female OW swimmers had skinfolds similar to their contemporary OW swimmers but were lower than earlier reports of OW swimmers; however, they were higher than those of pool swimmers. Male and female OW swimmers had 9% and 6% lower LMI, respectively, than pool swimmers. Lower body mass and LMI were correlated with better World Championships finishing positions (R2=.46, P=.0151, and R2=.45, P=.0177, respectively). These data are a unique report of elite OW swimmers` physiques around international competition and demonstrate a potential morphological optimization in OW swimmers that warrants further investigation in larger populations.